Fiscal dominance in the West African Monetary Zone: An empirical investigation - Ibrahima Diallo; Isatou Mendy (West African Journal of Monetary and Economic Integration, 2018)
This paper investigates the existence or otherwise of Fiscal dominance (non-Ricardian) regime in the West African Monetary Zone (WAMZ) from 1990 through 2017 using a Structural Vector Auto Regressive (SVAR) approach. Following Canzoneri, Cumby and Diba (2000), the study made use of public liabilities and primary balance as the main variables of the model. Our findings confirm the existence of fiscal dominance regime in Ghana, Guinea and Sierra Leone, and monetary dominance regime in The Gambia and Nigeria. The main policy recommendations proffered are that fiscal policy should be based on an active reaction function for countries with fiscal dominant regimes in order to allow primary surplus respond to change in debt thereby ensuring credibility and solvency. For those that exhibit Recardian regimes phenomena, they should have robust and effective monetary policy re-enforced by strong and efficient institutions, autonomous and devoid of any fiscal interference and policy accommodation that may lead to inflation bias.
Keywords: C32; E58; E62; 330; Fiscal Dominance; Fiscal and Monetary Policy; SVAR; WAMZ